The Religion of The Muslims of Medieval and Early Modern Castile: Interdisciplinary Research and Recent Studies on Mudejar Islam (2000-2014) (EN) (Edad Media. Revista de Historia, 2017)
The present article examines recent contributions to the study of Islam and Muslim communities in Medieval and Early Modern Castile (2000-2014). Our aim is to identify the main areas of focus, the topics and the key issues addressed by scholars in the field; and to consider the significance of the new findings to the existing body of knowledge of Islamic sources and of the practice of Islam in Castile. It will be argued that recent scholarship in this area demonstrates its rich possibilities for an innovative, interdisciplinary approach towards Islam as a lived minority religion.
Keywords: Castile; Islamic practices; material religon; methods; moriscos; m; mudejars; recent scholarship